Interplay between the abdominopelvic radiotherapy and gut microbiota - Chenxiang, Ding; Jing, Zhuang; Xiaojian, Yu; Hua, Xie; Xi, Yang (Frontiers in Microbiology, 2025)
Radiotherapy is a crucial treatment modality for abdominopelvic malignancies, with particularly significant effects on the gut microbiota. A reciprocal relationship exists between abdominopelvic radiotherapy and the gut microbiota. The gut microbiota plays vital roles in maintaining host health, modulating immune responses, and regulating metabolic functions. Abdominopelvic radiotherapy induces significant alterations in both the diversity and abundance of the gut microbiota, which may be critically involved in the development of radiotherapy-related adverse effects and the compromised therapeutic efficacy. Concurrently, the distinct biological properties of the gut microbiota and its derivatives can also influence the host response to radiotherapy. Understanding this interplay between abdominopelvic radiotherapy and the gut microbiota is of paramount importance for improving patient quality of life and treatment outcomes. This review discusses the impact of abdominopelvic radiotherapy on gut microbiota composition and summarizes recent advances in microbiota-targeted interventions aimed at radioprotection and radiosensitization, providing a theoretical foundation for optimizing radiotherapy for abdominopelvic malignancies.